METHODOLOGICAL ASPECTS OF DEVELOPING THE CONTENT OF HIGHER PEDAGOGICAL EDUCATION UNDER CONDITIONS OF IMPLEMENTATION OF FGOS 3 ++ - Andzhela Mukharbievna Shekhmirzova (Science and Innovation Center Publishing House, 2019)
This article is devoted to the main methodological aspects of developing the content of higher pedagogical education in accordance with state goals in accordance with the social order of modern society, the methodological basis of which is assessed by educational and professional standards. Methodological problems of the lack of conformity of goals and content of higher pedagogical education are surveyed. The role of competencies in improving the quality of teacher training, taking into account global trends in the development of higher education, is examined. The ways of solving the problem of matching goals with the formulation of the content of higher pedagogical education adequate to them are indicated.